Aldol condensation of furfural and methyl isobutyl ketone over Zr-MOF-808/silica hybrid catalysts. (1st May 2023) - Morales, Gabriel; Paniagua, Marta; de la Flor, Daniel; Sanz, María; Leo, Pedro; López-Aguado, Clara; Hernando, Héctor; Orr, Samantha A.; Wilson, Karen; Lee, Adam F.; Melero, Juan A.
Graphical abstract: Highlights: Preparation of Zr-MOF-808/silica hybrid catalysts. Preservation of structure integrity and incorporation of metalorganic phase on mesoporous silica. Boosting of the catalytic performance in the aldol condensation of furfural and MIBK. Highly active, selective and stable catalyst for the production of bio jet-fuel precursors. Abstract: Mesoporous silica-supported Zr-MOF-808 catalysts have been synthesised and tested in the aldol condensation of (biomass-derived) furfural and methyl isobutyl ketone to bio-jet fuel precursors. Growth of Zr-MOF-808 nanocrystals over silica scaffolds results in well-dispersed Zr species which confer strong Lewis acidity as determined by FTIR of chemisorbed pyridine. Hybrid Zr-MOF-808/silica materials exhibit higher condensation activity than the unsupported crystalline Zr-MOF-808 (which is also prone to rapid deactivation). Textural properties of the silica support strongly influence the catalytic performance, with a high surface area and sufficiently large mesopore desirable. In the screening, the optimum Zr-MOF-808/MCM-41 catalyst delivered 68 % furfural conversion and 90 % selectivity to the C11 aldol adduct, 1-(furan-2-yl)-5-methylhex-1-en-3-one, at 130 °C and a furfural:Zr mass ratio of 150:1. Although more stable than the pure Zr-MOF-808, the Zr-MOF-808/MCM-41 also suffered significant deactivation over successive condensation reactions due to strongly adsorbed organic residues, however this was largely ameliorated by decreasing the furfural:Zr ratio to 75:1, which also led to an outstanding catalytic performance (100 % furfural conversion and adduct selectivity), likely because of the suppression of furfural polymerization.